Edukasi Pemilahan dan Pengelolaan Sampah Bagi Siswa SMP Islam Yayasan Nurul Iman - Riana, Riska Iva; Syamsuriah, Syamsuriah; Irawanda, Gita; Mus, Sumarlin; Tompong, By Tri Agung Nusantara Kr. J. (KARYA: Journal of Educational Community Service, 2025)
Proper waste management begins with individual awareness, particularly from an early age. This Community Service Program aimed to enhance the knowledge, attitudes, and behaviors of students in sorting and managing waste according to its types: organic, inorganic, and hazardous-toxic (B3) waste. The activity was conducted at SMP Islam Yayasan Nurul Iman, involving 60 students selected from various grade levels as the primary subjects. The program employed an educative-participatory approach through stages, including socialization, hands-on simulation, and the installation of segregated waste bins. Evaluation was carried out using pre-test and post-test instruments, revealing a 40%–50% increase in students’ understanding across five key waste management indicators. In addition to cognitive improvement, students also demonstrated positive behavioral changes in disposing of waste properly. The program received strong support from school staff and teachers and showed a multiplier effect, as students began applying waste sorting practices at home. These findings indicate that appropriate educational interventions and active student involvement can foster a sustainable culture of environmental awareness within schools.